The modern clinician's guide to working with LGBTQ+ clients : the inclusive psychotherapist - Nichols, Margaret Elizabeth, 1947- (New York, NY : Routledge, 2021)
"The Modern Clinician's Guide to Working with LGBTQ Clients is a ground-breaking resource for therapists working with LGBTQ clients whose identity expressions span all gender, sex, and relationship diverse groups. With a wealth of therapeutic strategies and case studies, this resource helps professionals respond to this 'big tent' community in an informed and empathetic way"--
Introduction: Grad school didn't prepare you for this -- From bad to mad to civil rights : a history of deviance and acceptance of same sex attracted people -- The roads converge again : how the 'T' got added to the LBG -- The big tent and intersectionality -- Exactly what are we studying, anyway, and what does it mean? -- Who is gay? -- The twentieth century gay and lesbian client -- Today's gay and lesbian client -- Issues of gay men and boys -- Gay male couples -- Counseling lesbians -- Lesbian couples -- Bi any other name- science grapples with multiple gender attractions -- Clinical issues of bisexually identified clients -- Aces and Aros -- Pansexuals, mono vs. Multisexuals, sexual fluidity -- From two genders to many -- Working with adult transgender clients -- Working with the transgender adolescent -- The gender expansive child -- Non-binary identities and gender fluidity -- BDSM comes out of the shadows -- Working with kinky clients -- Introduction to consensual nonmonogamy -- Working with clients who are non-monogamous -- and those who want to be -- Conclusion: The tangled path forward.
OCLC-licensed vendor bibliographic record.
Keywords: Sexual minorities -- Psychology; Sexual minorities -- Mental health; Sex (Psychology); Psychotherapy; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health